Morphological changes of a retina of an eye at influence by laser radiation of threshold intensity with wavelenght 450 nm and their correction by synthetic dipeptid - Ye. Yu. Anikina; A. V. Potapov; Ye. Yu. Varakuta; I. V. Bukhtiyarov; Yu. Yu. Kislyakov; A. B. Prokofiyev; Ye. A. Kamenkova; S. V. Logvinov (Бюллетень сибирской медицины, 2009)
The analysis of alterations retina of during exposure of threshold laser intensity and opportunities to correct it by synthethic dipeptid. The material and method: 23 rabbits were included in the experiment. Recived matherial was investigated with help of light and electron microscopy. All layers of retina were damaged during laser exposure. The usage of synthethic dipeptide reduced laser damage. Synthethic dipeptid have retinoprotection abilities.